2009
DOI: 10.1242/jeb.028670
|View full text |Cite
|
Sign up to set email alerts
|

Radio frequency magnetic fields disrupt magnetoreception in American cockroach

Abstract: SUMMARYThe sense that allows birds to orient themselves by the Earth's magnetic field can be disabled by an oscillating magnetic field whose intensity is just a fraction of the geomagnetic field intensity and whose oscillations fall into the medium or high frequency radio wave bands. This remarkable phenomenon points very clearly at one of two existing alternative magnetoreception mechanisms in terrestrial animals, i.e. the mechanism based on the radical pair reactions of specific photosensitive molecules. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 33 publications
5
49
0
Order By: Relevance
“…These studies provide only a qualitative indication of the RF response: either the RF field produces a statistically significant response or it does not, making it difficult to verify that the observed effects arise from a radical pair mechanism. Attempts have been made to prove a resonance response by finding the threshold RF field strength when on and off resonance with a static field: 30,31 based on the spin-locking phenomena we now propose a definitive test. Applying an on-resonance RF field orthogonal to the static field we can expect an RF response to appear when a threshold RF field strength is exceeded and that this response will disappear again at a higher RF field strength as the radical pair becomes spin-locked and the net RF effect decreases as B 0 1 is approached.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These studies provide only a qualitative indication of the RF response: either the RF field produces a statistically significant response or it does not, making it difficult to verify that the observed effects arise from a radical pair mechanism. Attempts have been made to prove a resonance response by finding the threshold RF field strength when on and off resonance with a static field: 30,31 based on the spin-locking phenomena we now propose a definitive test. Applying an on-resonance RF field orthogonal to the static field we can expect an RF response to appear when a threshold RF field strength is exceeded and that this response will disappear again at a higher RF field strength as the radical pair becomes spin-locked and the net RF effect decreases as B 0 1 is approached.…”
Section: Discussionmentioning
confidence: 97%
“…A number of in vivo RY-DMR studies have been carried out on birds [28][29][30] and insects 31 in order to determine the origin of their magnetic sensitivity. These studies provide only a qualitative indication of the RF response: either the RF field produces a statistically significant response or it does not, making it difficult to verify that the observed effects arise from a radical pair mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for a RPM-based magnetic compass in some animals includes: (1) sensitivity to the axis, but not polarity, of the magnetic field ( Fig.1) (Wiltschko and Wiltschko, 1972;Phillips, 1986); (2) involvement of a light-dependent magnetoreception mechanism (Phillips and Borland, 1992a;Phillips and Borland, 1992b;Phillips and Sayeed, 1993;Freake and Phillips, 2005;Wiltschko and Wiltschko, 2005;Vacha et al, 2008b); (3) disruption of magnetic compass orientation outside a narrow window of static field intensities ; (4) the absence of an effect of 'pulse remagnetization' (Beason and Semm, 1996;Munro et al, 1997a;Munro et al, 1997b); and (5) disruption by low-level alternating fields (~0.1% of the static field strength) in the low RF range (<100MHz) that should alter the magnetic field-dependent populations of singlet and triplet energy states in a RPM (Ritz et al, 2004;Ritz et al, 2009;Henbest et al, 2004;Thalau et al, 2005;Vacha et al, 2009). In migratory birds, the effects of low-level RF fields have been shown to depend on both the intensity and relative alignment of the static magnetic field (Ritz et al, 2004;Ritz et al, 2009) .…”
Section: The Radical Pair Mechanismmentioning
confidence: 99%
“…Ritz et al, 2004;Henbest et al, 2004;Thalau et al, 2005;Ritz et al, 2009;Vacha et al, 2009) has important implications for designing experiments to investigate the role of magnetic cues in rodent spatial behavior. In a study of migratory birds exposed to a RF field tuned to the Larmor frequency (the precession frequency of the magnetic moment of an electron around an external field), Ritz et al (Ritz et al, 2009) found that magnetic compass orientation was disrupted at an intensity of 15nT but not 5nT, which roughly bracketed background levels of ambient radio frequency interference (RFI); for comparison, the geomagnetic field is ~50,000nT.…”
Section: Appendixmentioning
confidence: 99%
“…The magnetoreception of insects and some mammals has also been shown to be sensitive to RF bias (Vacha et al, 2009;Malkemper et al, 2015, respectively), while mole-rats (Thalau et al, 2006) did not react to an RF field. The opportunity to investigate amphipod magnetic orientation in an Antarctic ecosystem devoid of electromagnetic noise sources led us to two main questions: (1) is there any disruptive effect of RF fields on the magnetosensitivity of marine isopods; and if so, (2) what is the RF field flux density threshold?…”
Section: Introductionmentioning
confidence: 99%